Contribution to the study of pseudouremias - Tolentino Melgarejo, Pedro (1939)
Since ancient times it has been studied in the chapter on symptomatic Uremia a whole wealth so varied and diverse that it was difficult to holistic understanding; attempts to establish clarity on this issue created clinical forms, whose numerical possibilities seemed endless, because for this emphasis was placed not only the most committed organic systems but to the prevalence of a symptom, and in this vein was talk of uremia nervous, visceral, gastrointestinal, respiratory, uremia asthma, seizure, psychotic, amaurósica, etc .; secondly all attempts explanation pathogenic under one hypothesis.